PERTIMBANGAN PEMINDAHAN IBUKOTA NEGARA DITINJAU DARI PERSPEKTIF GEOGRAFI PERTAHANAN - Supriyatno, Makmur (Indonesia Defense University, 2013)
The discourse on the transfer of the capital city of Jakarta has been conducted intensively lately, especially after the five-year flood hit Jakarta in January 2013. Consideration to use variety of scientific approaches have been expressed by various experts of regional development or urban planning in order to provide input where actual capital city should be moved. Defense aspect is actually one of important aspect to be considered in regards of transfers of the state capital. One of the defense branches of the specifics that need careful attention is the geography of defense. Since the Roman times to present the geography of defense is considered as a fortification or defense and even as central of gravity,although all regions of the country has been controlled. However, if the capital has not been occupied and controlled by the enemy, then the enemy could not be said to have mastered. To that end, the capital need to get treatment as a fortress that must qualify and meet variety of indicators from the perspective of defense. Thus, the discourse of the transfer of the capital need an indicator of the State Capital from the perspective of defense. Therefore, the transfer of the state capital has included sharing scientific considerations, including geography of defense.Â Keywords: Capital City, Transfers of Capital, Defense, Geography of Defense.